2013
DOI: 10.1111/lam.12028
|View full text |Cite
|
Sign up to set email alerts
|

Micro-encapsulation of ozonated red pepper seed oil with antimicrobial activity and application to nonwoven fabric

Abstract: Significance and Impact of the Study: This is the first report on the antimicrobial action of RPSO after ozonation process. These findings suggest that ozonated red pepper seed oil (ORPSO) may be a useful and effective antimicrobial agent against the micro-organisms with antibiotic resistance. Therefore, as a natural product, RPSO represents a sustainable alternative to the use of synthetic antimicrobial agents. To our knowledge, this is also the first time that ORPSO has been micro-encapsulated for the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 56 publications
0
29
0
1
Order By: Relevance
“…Some medical investigators consider that red pepper seeds can take precautions against cardiovascular disease and regulate the central nervous system. Red pepper seeds also contain various minerals and the vitamins A, D, E, and K, and its high level of vitamin E is especially helpful to health care and anti‐aging (Ozyildiz and others ; Wang and others ). Microencapsulation of ozonated red pepper seed oil for the preparation of functional textile material gave higher antimicrobial activity than nonmicroencapsulated oil (Ozyildiz and others ).…”
Section: Benefits Of Oils and Their Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some medical investigators consider that red pepper seeds can take precautions against cardiovascular disease and regulate the central nervous system. Red pepper seeds also contain various minerals and the vitamins A, D, E, and K, and its high level of vitamin E is especially helpful to health care and anti‐aging (Ozyildiz and others ; Wang and others ). Microencapsulation of ozonated red pepper seed oil for the preparation of functional textile material gave higher antimicrobial activity than nonmicroencapsulated oil (Ozyildiz and others ).…”
Section: Benefits Of Oils and Their Encapsulationmentioning
confidence: 99%
“…They give plants their characteristic odors and are a common source of bioactive ingredients. In addition to basic nutrition, they are consumed for their various functional properties including uses such as gastronomic, nutritional, organoleptic, antioxidant, anti‐inflammatory, antivasoconstrictive, anti‐arrhythmic, antithrombotic, antimicrobial, antihypertension, antiulcer, anti‐aging, anticancer, antidiabetic, antidepressant, antipyretic antitussive, antidandruff, antinociceptive, and insect repellent (Satchell and others ; Zhao and others ; Deng and others ; Nadig and Laxmi ; Williams and others ; Mandal and Mandal ; Chung and others ; Ozyildiz and others ; Che Idris and others ; Ito and others ; Jeena and others ; Jouki and others ; Lockyer and Rowland ; Olmedo and others ; Szabo and others ). Marine, vegetable, and essential oils have recently gained a great popularity and scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…The γ‐tocopherol has been found to be more effective than mixed tocopherols in protecting against certain specific types of oxidative damage (Singh et al, ). Özyildiz, Karagönlü, Basal, Uzel, and Bayraktar () found that the ozonated red pepper seed oil was a useful and effective antimicrobial agent against the growth of antibiotic‐resistant micro‐organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The coacervation, based on the phase separation of one or many hydrocolloids, is divided into as simple and complex coacervation. While the simple coacervation involves the use of a single polymer in organic or aqueous media, the complex coacervation involves the use of two oppositely charged polymeric materials [13].…”
Section: Introductionmentioning
confidence: 99%